Anterior eye health recording. Issue 4 (August 2015) - Wolffsohn, James S.; Naroo, Shehzad A.; Christie, Caroline; Morris, Judith; Conway, Robert; Maldonado-Codina, Carole; the British Universities Committee of Contact Lens Educators (BUCCLE)
Abstract Aims To survey eye care practitioners from around the world regarding their current practice for anterior eye health recording to inform guidelines on best practice. Methods The on-line survey examined the reported use of: word descriptions, sketching, grading scales or photographs; paper or computerised record cards and whether these were guided by proforma headings; grading scale choice, signs graded, level of precision, regional grading; and how much time eye care practitioners spent on average on anterior eye health recording. Results Eight hundred and nine eye care practitioners from across the world completed the survey. Word description (p < 0.001), sketches (p = 0.002) and grading scales (p < 0.001) were used more for recording the anterior eye health of contact lens patients than other patients, but photography was used similarly (p = 0.132). Of the respondents, 84.5% used a grading scale, 13.5% using two, with the original Efron (51.6%) and CCLRU/Brien-Holden-Vision-Institute (48.5%) being the most popular. The median features graded was 11 (range 1–23), frequency from 91.6% (bulbar hyperaemia) to 19.6% (endothelial blebs), with most practitioners grading to the nearest unit (47.4%) and just 14.7% to one decimal place. The average time taken to report anterior eye health was reported to be 6.8 ± 5.7 min, with the maximum time available 14.0 ± 11 min. Conclusions Developed practice and research evidence allows best practice guidelines for anterior eye health recording to be recommended. It is recommended to: record which grading scale is used; always grade to one decimal place, record what you see live rather than based on how you intend to manage a condition; grade bulbar and limbal hyperaemia, limbal neovascularisation, conjunctival papillary redness and roughness (in white light to assess colouration with fluorescein instilled to aid visualisation of papillae/follicles), blepharitis, meibomian gland dysfunction and sketch staining (both corneal and conjunctival) at every visit. Record other anterior eye features only if they are remarkable, but indicate that the key tissue which have been examined.